Individual and simultaneous degradation of sulfamethoxazole and trimethoprim by ozone, ozone/hydrogen peroxide and ozone/persulfate processes: A comparative study - Adil, Sawaira; Maryam, Bareera; Kim, Eun-Ju; Dulova, Niina (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
This study investigates the individual and simultaneous degradation and mineralization of the antibiotics, sulfamethoxazole (SMX) and trimethoprim (TMP) in aqueous solution by ozonation, ozone-activated persulfate (PS) and hydrogen peroxide (H2O2) processes. The trials were carried out in a semi-continuous column bubble reactor with an ozone diffuser located at the bottom of the column for a period of 2 h. Furthermore, the efficiency of studied processes were evaluated at two different initial pH and various doses of oxidants. The target compounds degradation observed pseudo-first-order rate constants (k(obs)) and removal of total organic carbon (TOC) using ozone-based oxidation processes were compared. Irrespective of the applied processes, the mineralization of target compounds was less effective than their degradation in both individual and simultaneous systems. The highest antibiotics degradation rate constants were observed for individual oxidation of TMP (k(obs) = 0.379 min(-1)) and SMX (k(obs) = 0.367 min(-1)) at alkaline initial pH (pH(0)) in the O-3/H2O2 system at an [antibiotic]/H2O2 molar ratio of 1/1. Irrespective of the antibiotic studied, the most effective TOC removal (similar to 44%) was observed after a 2-h treatment with the O-3/H2O2 system at an [antibiotic]/H2O2 molar ratio of 1/5 (pH(0) 10.9). The O-3 /PS system at an [antibiotic]/PS molar ratio of 1/5 (pH(0) 10.9) proved the most effective system for both mineralization and degradation (k(obs) values of 0.294 min(-1) and 0.266 min(-1)) of TMP and SMX, respectively, during the simultaneous oxidation of SMX-TMP. The decomposition by-products of SMX and TMP in studied ozone-based processes were identified using LC-MS analysis. The results of this study strongly suggest that using the O-3 /PS process is a promising solution to reduce SMX-TMP contamination in water matrices.
Keywords: ADVANCED OXIDATION PROCESSES; ACTIVATED PERSULFATE OXIDATION; TRANSFORMATION PRODUCTS; EMERGING CONTAMINANTS; WASTE-WATER; ANTIBIOTIC SULFAMETHOXAZOLE; PHOTOCATALYTIC OZONATION; SOLAR PHOTODEGRADATION; FENTON-LIKE; KINETICS